Production and prosperity in the Theodosian period (Leuven ; Walpole, MA)
xvi, 397 sayfa
Keywords: “Despite the large increase in material evidence datable to the Theodosian period (379-455 C.E.), textual sources still dominate our view of the period. This has led to a pretty bleak picture made up of foreign invasions, loss of territory, a weak ruler dynasty, a state-driven distribution system, and declining cities. And yet, many regions of the Roman Empire seem to have been doing quite well. For this reason, this volume aims at a re-evaluation of the prosperity of the Roman Empire under the Theodosii. Archaeological, historical, epigraphic and numismatic research are combined to investigate the vitality and socio-economic potential of distinct regions of the empire; to explore the relative importance of cities, villages, fortresses and estates in patterns of purchase and comsumption; to gain insights into the mechanisms and forces underlying production, distribution and consumption of both staple goods and luxury products; and, eventually, to offer explanations for the general condition and functioning of the empire.” --